Approaches towards a critical evaluation and update of the red list of South African Butterflies - Ball, Johathan Bradford (Stellenbosch : Stellenbosch University, 2006)
Thesis (MScConsEcol (Conservation Ecology and Entomology))--University of Stellenbosch, 2006.